Vacuum-assisted excision: a safe minimally invasive option for benign phyllodes tumor diagnosis and treatment—a systematic review and meta-analysis - Gil, Maria Luísa Braga Vieira; Coelho, Bertha Andrade; Couto, Henrique Lima; Silva, Henrique Moraes Salvador; Pessoa, Eduardo Carvalho; Sharma, Nisha; Mann, Ritse; McIntosh, Stuart A.; Diniz, Paulo Henrique Costa; Cantidio, Farley Soares; Gil, Gabriel Oliveira Bernardes; Salvador, Anna Dias; et al. (Frontiers in Oncology, 2024)
Synopsis This is a systematic review and meta-analysis comparing surgical excision with percutaneous ultrasound-guided vacuum-assisted excision (US-VAE) for the treatment of benign phyllodes tumor (PT) using local recurrence (LR) as the endpoint. Objective To determine the frequency of local recurrence (LR) of benign phyllodes tumor (PT) after ultrasound-guided vacuum-assisted excision (US-VAE) compared to the frequency of LR after surgical excision. Method A systematic review and meta-analysis [following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard] was conducted by comparing LR in women older than 18 years treated for benign PT by US-VAE compared with local surgical excision with at least 12 months of follow-up. Studies were retrieved from PubMed, Scopus, Web of Science, and Embase. The pooled effect measure used was the odds ratio (OR) of recurrence. Results Five comparative prospective or retrospective observational studies published between January 1, 1992, and January 10, 2022, comparing surgical excision with percutaneous US-VAE for LR of benign PT met the selection criteria. Four were retrospective observational cohorts, and one was a prospective observational cohort. A total of 778 women were followed up. Of them, 439 (56.4%) underwent local surgical excision, and 339 (43.6%) patients had US-VAE. The median age of patients in the five studies ranged from 33.7 to 39 years; the median size ranged from 1.5 cm to 3.0 cm, and the median follow-up ranged from 12 months to 46.6 months. The needle gauge ranged from 7G to 11G. LR rates were not statically significant between US-VAE and surgical excision (41 of 339 versus 34 of 439; OR 1.3; p = 0.29). Conclusion This meta-analysis suggests that using US-VAE for the removal of benign PT does not increase local regional recurrence and is a safe minimally invasive therapeutic option. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022309782.